FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INDUSTRI HALAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sholehoddin, Moh; Kunaifi, Aang; Rokib, Moh; Arif, Moh; Falahuddin; Amin, Moh Rokibul (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
In recent years, the halal sector has been regarded as the source of the country's economic growth. Indonesia has great potential for developing halal industries as it is the country with the largest Muslim population in the world. According to The State of Global Islamic Economy Report 2020-2021, Muslims around the world spend more than 2.02 trillion on goods like halal food, halal pharmacy, halal cosmetics, fashion, Shariah tourism, and more. In addition, according to the Indonesian Shariah Economic Master Plan 2019-2024, Indonesia is the 10th largest buyer in any halal industry subsector. Indonesia ranks first in the world for food shopping and fifth for halal travel. A deductive study is a type of research that begins with a theory or hypothesis and seeks to test its validity through data collection and analysis. The results of the research show that the factors affecting the value of halal industry in companies listed on the Indonesian stock exchange must have a halal certification from MUI. Halal certification is a process of systematic testing to find out whether a product made by a company meets legal requirements or not.